The predictors and the prognostic significance of axillary lymph nodes involvement in breast cancer - Bakkour, Amine Mohammed; Surriah, Mohammed Hillu; Al-Imari, Amir Naif Kadum; Al-Asadi, Riad Rahman Jallod (International Surgery Journal, 2019)
Background: Breast cancer is the most common cancer among women worldwide. The presence of axillary lymph node metastases in breast cancer is an important factor in assessing prognosis and determines management after surgery. The study aimed at identification of the factors that predict axillary lymph node involvement in CA breast. Addressing the prognostic effect of axillary lymph node involvement in turn of predicting the recurrence of CA breast. Methods: This is a prospective review of one hundred cases of Ca breast who have underwent modified radical mastectomy and axillary clearance at Al-Karama Teaching Hospital during the period from January 2014 to December 2018. Results: Positive axillary involvement was found in (74/100, 74%). The highest occurrence of positive axilla was found in (less than 30 and 30-39 years) age groups (27/74, 36%) with the outer quadrants (upper and lower) constituting the majority (50/74, 68%). Positive axillary involvement was mostly notified in tumor grade T4 (39/74, 53%) and in poorly differentiated lesions (47/74, 64%). The highest recurrence rate was found in patients with positive axillary metastases (12/74, 16%), nodal involvement of ten or more nodes (9/41, 22%), nodes with extracapsular extension (10/51, 20%) and in patients who have not taken and/or completed their chemo-radiation sessions (9/11, 82%). Conclusions: Positive axillary lymph node involvement was seen mostly in: young age patients, outer quadrant lesions, tumors with skin involvement, and poorly differentiated lesions.